The expression of bone morphogenetic proteins in osteosarcoma and its relevance as a prognostic parameter. Issue 5 (1st May 2002) - Sulzbacher, I; Birner, P; Trieb, K; Pichlbauer, E; Lang, S
Abstract : Aims: The expression of bone morphogenetic proteins (BMPs) was analysed in 47 osteosarcomas to determine differences in the expression of BMP subtypes and to correlate expression with response to chemotherapy, in addition to the disease free and overall survival of patients. Methods: The expression of BMPs was examined immunohistochemically in 47 biopsy specimens of osteosarcoma using commercially available antibodies against different subtypes (BMP-2/4 (A-20), BMP-3 (N-19), BMP-4 (N-19), BMP-5 (N-19), BMP-6 (N-19), BMP-7 (N-19), BMP-8 (N-19)). The avidin–biotin–immunoperoxidase method was used for all antibodies. Results: The expression of BMP subtypes varied considerably: 28 of the 47 tumours expressed BMP-2/4, 24 expressed BMP-3, 41 expressed BMP-5, 31 expressed BMP-6, 43 expressed BMP-7, and 42 expressed BMP-8. High expression of BMP-6 was found in those parts of the osteosarcoma with a chondroid differentiation (p = 0.016, Mann-Whitney test). No correlation was observed between the response to chemotherapy and the expression of BMPs (p > 0.05, Mann-Whitney test). Univariate analysis showed no correlation between overall survival or progression free survival and the expression of BMPs (p > 0.05, log rank test). Conclusions: BMP-7 and BMP-8 are highly expressed in osteosarcoma. Moreover, high expression of BMP-6 correlates with a chondroid differentiation. In contrast to conclusions derived from previous studies in which small numbers of tumours were investigated, these results indicate that the expression of BMPs does not help to predict the outcome of patients.